THE CAUSES OF DEPRESSION AMONG ADOLESCENTS AT UNIVERISTI MALAYSIA SABAH - Rahmat bin Abdullah; Mahathir Mohammad bin Rahim; Mohd Alizwan bin Mohammad Asyri; Mohamad Zul Ilman bin Ramza; Caroline Geetha (Malaysian Journal of Business and Economics (MJBE), 2022)
This study aims to identify what are the causes of depression among a sample of adolescents in Universiti Malaysia Sabah. Among the reasons surveyed by researchers were family conflict, financial difficult, exam pressure and assignment induce psychogenic headaches and also social media. The quantitative of all acquisition data is based on the survey through the distribution of questionnaires to 54 respondents selected at random and also research from the previous study. The results of the survey was measured using reliability analysis and correlation coefficient for each independent variable determined. In addition, the implementation of an approach to measure the level of depression for each respondent was made using the Beck Depression Inventory assessment. At the end of this study, the results found that only one factor was significant in promoting the symptoms of depression among adolescents at Universiti Malaysia Sabah that is the influence of social media. There is a positive relationship between the uses of social media among adolescents to the reason they suffer from depression. The results confirmed that the use of social media could increase depression and loneliness among adolescents in Universiti Malaysia Sabah.